Defining the north Australian monsoon onset: A systematic review. (June 2020) - Lisonbee, Joel; Ribbe, Joachim; Wheeler, Matthew
The annual Australian monsoon pattern includes an onset, or the much anticipated first active monsoon period of the season, but defining the monsoon onset has proven to be problematic. Since the first Australian monsoon onset definition by Troup in 1961 there have been many others presented. There appears to be no universally accepted method to define the Australian monsoon onset, and therefore, we present here an analysis of the methods that have been proposed. The aim of this paper is to systematically review the different methods used to define the Australian monsoon onset, adding to the work that has been done by other reviews for monsoon systems around the world. For the first time, we identify the 25 different methods that have been published for the Australian monsoon/wet season onset and compare them to identify how well they align. When considering the 57 seasons where more than one onset definition is provided, the range of dates within the season can range over several months, with an average range of 44 days and the largest range within a season of 78 days. Thus, we show that different onset definitions are capturing different events altogether and pin the 'onset' to different dates throughout the progression of the north Australian wet season. Some capture a 'wet season onset' while others capture the dynamical overturning of the atmosphere (i.e. the monsoon). In conclusion, our analysis finds that there is still a lack in real-time monitoring or prognostic capabilities of monsoon onset dates as well as limited operational applicability despite a plethora of definitions.